PULMONARY AND BIOCHEMICAL CHARACTERISTICS OF SMOKER AND NON-SMOKER MODERN DANCERS - KURTEL, HIZIR (SOC BRASILEIRA MED ESPORTE, 2016)
Introduction: Although the harmful effects of smoking on the cardiovascular and respiratory systems have been established for a long time, the effect on physiological and physical parameters in modern female dancers is not well documented. Objective: To determine differences in selected pulmonary functions, biochemical parameters, and body composition in female smoker and non-smoker modern dancers who are university or graduate students. Methods: A total of twenty-two female modern dancers (mean age of 24.6 +/- 4.3 years), who were non-smokers (n = 11) and smokers (n = 11), voluntarily participated in the study. The smokers had been smoking 1 to 20 cigarettes per day for an average period of seven years. The pulmonary function test Mir Spirobank Spirometer, (Italy) was applied; selected biochemical parameters were tested, and various anthropometric measurements (height, weight and seven skinfold thickness) were performed. The results of body composition were evaluated using Jackson-Pollock equations. Intergroup comparisons were performed using the Mann-Whitney U test. Result: No significant differences were found between smoker and non-smoker dancers in terms of body composition (body fat, % body fat, lean body fat) and selected biochemical parameters (p > 0.05). However, non-smokers had prediction values of forced expiratory volume during the first second (FEV1) and peak expiratory flow (PEF) significantly better (p < 0.05). The effect of smoking on the performance of female modern dancers should be examined in a longitudinal study, with a higher number of participants. Conclusion: It was observed that smoking reduces lung pulmonary capacity at a certain rate, although the biochemical parameters and body composition of the female smoker and non-smoker dancers were similar.
Keywords: tobacco; respiratory function tests; blood chemical analysis; adipose tissue; dancing; CONTEMPORARY DANCE; CIGARETTE-SMOKING; BALLET; PERFORMANCE; EXERCISE; FITNESS; SPORTS; BACK